Short stories of the civil rights movement : an anthology - Whitt, Margaret Earley, 1946- (Athens : University of Georgia Press, 2006)
A collection of twenty-three short stories by various African-American and white authors reflect the drive and power of ordinary citizens who influenced the civil rights movement.
See what tomorrow brings (1968) / James W. Thompson -- The first day of school (1958) / R.V. Cassill -- Neighbors (1966) / Diane Oliver -- Spring is now (1968) / Joan Williams -- The beginning of violence (1985) / Joanne Leedom-Ackerman -- The welcome table (1996) / Lee Martin -- Food that pleases, food to take home (1995) / Anthony Grooms -- Direct action (1963) / Mike Thelwell -- Doris is coming (2003) / Z Z Packer -- Negro progress (1994) / Anthony Grooms -- The marchers (1979) / Henry Dumas -- Moonshot (1989) / Alma Jean Billingslea-Brown -- Selma (1972) / Natalie L. M. Petesch -- Marching through Boston (1966) / John Updike -- The convert (1963) / Lerone Bennett Jr. -- Where is the voice coming from? (1963) / Eudora Welty -- Liars don't qualify (1961) / Junius Edwards -- Advancing Luna-- and Ida B. Wells (1977) / Alice Walker -- Means and ends (1985) / Rosellen Brown -- Going to meet the man (1965) / James Baldwin -- Flora Devine (1995) / Anthony Grooms -- Paying my dues (1996) / Val Coleman -- To my young husband (2000) / Alice Walker.
Black Issues Book Review.
Adult
Keywords: Civil rights movements -- Fiction; Short stories, American; Civil rights movements -- Fiction; Short stories; United States -- Race relations -- History -- 20th century -- Fiction; United States -- Race relations -- History -- Fiction